Estrategias para mejorar el desempeño de los trabajadores de la empresa VIPROBERI SEGURIDAD & PROTECCIÓN BECERRA RÍOS CIA. LTDA, de la ciudad de Quito, año 2022. - Andrade Quilligana, Darwin Joel (2023)
The main objective of this research work is to establish improvement strategies for the labor performance of workers in the company VIPROBERI SEGURIDAD Y PROTECCIÓN BECERRA RIOS, in the city of Quito. Obtaining as hypothesis of the investigation that the proposal of strategies of improvement if it influenced in the improvement of the labor performance of the workers of the company VIPROBERI SEGURIDAD Y PROTECCIÓN BECERRA RIOS. The methodology that was used was an exploratory and investigative investigation with the Analysis-Synthesis Method and to obtain data, the survey instrument was used, which was directed to the company's operational personnel, focusing on specific questions to the problem. The information obtained from the instrument that was applied was analyzed, where we were able to identify the aspects that the company should include in the personnel to achieve a better performance in their job, also their relationship with their colleagues in a favorable but not satisfactory work environment and the need for training to improve job performance. It was concluded that the company needs to propose strategies to improve the performance of its workers through the SWOT matrix, allowing it to generate training strategies and innovative tools to facilitate their activities. It is recommended that the proposed strategies be implemented and that they be followed up after implementation by measuring the degree of compliance.